Prognostic value of sentinel lymph node biopsy in melanomas of different Breslow’s thickness (Swiss Medical Weekly, 2016)
BACKGROUND: Although sentinel lymph node biopsy (SLNB) is the most sensitive and accurate investigative modality for establishing regional node status in patients with melanoma, its role and benefit in melanoma of different Breslow’s thickness is still controversial. OBJECTIVE: The current study aimed mainly to evaluate the effects of SLNB results on important outcome parameters in primary melanomas with different Breslow’s thicknesses. METHODS: In a retrospective cohort (1990 to 2014), all cases of single, primary localised cutaneous melanoma tumours were evaluated. Data collected consisted of tumour location, tumour type, ulceration, Breslow’s thickness and SLNB result. In addition, locoregional recurrence, distant metastases, disease-free and overall survival were used as the important parameters to compare outcome among the various groups in the current study. RESULTS: A total of 1111 patients (527 female, 584 male; mean age 64.33 ± 15.44 years) were considered in the analyses in this study, with mean follow-up of 22 77.3 days. The multivariate Cox analysis showed that age, ulceration, Breslow’s depth and SLNB result significantly decreased disease-free survival. This analysis also demonstrated that age, gender, ulceration, Breslow’s depth and SLNB result significantly affected overall survival. Furthermore, the Kaplan-Meier method showed that the patients with negative SLNB had longer disease-free survival than the patients with positive SLNB in thin, intermediate and thick melanomas (p